Global Trends and Contributions of Internet of Things (IoT) Research in Education: A Bibliometric Analysis - Rasyid, Rustam Efendy; Aisa, Sitti; Rizal, A. (Mimbar Ilmu, 2024)
The development of Internet of Things (IoT) technology has significantly transformed various sectors, including education. However, research on the implementation of IoT in education remains fragmented and lacks a comprehensive understanding of global trends and its contributions to educational advancements. This study aims to provide a holistic overview of global trends and contributions in IoT research within the educational field through bibliometric analysis of Scopus data from 2016 to 2024. The study adopts a qualitative descriptive approach using the PRISMA method to conduct a systematic literature review. The analyzed data comprises scientific publications related to IoT in education retrieved from the Scopus database. Bibliometric analysis was conducted to identify publication trends, prominent authors, contributing institutions, and dominant fields of study in this research area. The results indicate that the number of publications on IoT in education fluctuated annually, with a general upward trend peaking in 2023 before declining in 2024. The study identified Mershad, K. as the most prolific author and the Arts, Sciences, and Technology University as the leading institution contributing to IoT research in education. The dominant fields of study in these publications were Computer Science, followed by Social Sciences and Engineering, reflecting the multidisciplinary nature of IoT research in education. This study concludes that the application of IoT in education continues to evolve and significantly contributes to educational innovation.